THE INFLUENCE OF ENTREPRENEURIAL EDUCATION, SELF EFFICACY, LOCUS OF CONTROL, ON THE ENTREPRENEURSHIP INTENTIONS OF SMKN 3 JAKARTA STUDENTS - Shah, Azmi Auliya; Eryanto, Henry; Munawaroh (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study was conducted to determine the effect of entrepreneurship education, self-efficacy, locus of control, on the entrepreneurial intentions of students at SMK Negeri 3 Jakarta. The research was conducted by survey research method with a sample of 191 students and using proportional random sampling technique. In collecting data, researchers used a questionnaire and analyzed using multiple linear regression techniques to test the validity and reliability. From the results of the research that has been carried out, it shows that entrepreneurship education, self-efficacy, locus of control on entrepreneurial intentions among students. Therefore, teachers in the school environment are required to encourage entrepreneurship education, self-efficacy, locus of control, towards entrepreneurial intentions through various programs and entrepreneurship education to increase and explore students’ entrepreneurial intentions.